Environmental parameters factors exploration on lettuce seed germination with hydrogel - Huang, Yanhua; Chang, Yanbin; Ni, Zheng; Wang, Lizhi (Frontiers in Plant Science, 2024)
Lettuce (Lactuca sativa) germination is sensitive to environmental conditions. Recently, hydrogel has received increased attention as an alternative media to soil for seed germination. Compared to soil seeding, hydrogel-aided germination provides more controlled seeding environments.However, there are still challenges preventing hydrogel-aided seed germination from being widely used in industry production or academic studies, such as hydrogel formulation variations, seeding operation standardization, and germination evaluation. In this study, we tested how the combination of multiple environmental conditions affect lettuce seed germination time, which is measured as time needed for the first pair of leaves to appear (leaf emergence) or, alternatively, the third leaf to appear (leaf development). We found that germination time and success rate of two lettuce varieties (Iceberg A and Butter Crunch) showed different sensitivities to pH, Hoagland formulations and concentrations, light intensity, and hydrogel content. We have conducted statistical analysis on the correlation between germination time and these environmental conditions.